3D MoS2 Aerogel for Ultrasensitive NO2 Detection and Its Tunable Sensing Behavior. Issue 16 (10th July 2017) - Long, Hu; Chan, Leslie; Harley‐Trochimczyk, Anna; Luna, Lunet E.; Tang, Zirong; Shi, Tielin; Zettl, Alex; Carraro, Carlo; Worsley, Marcus A.; Maboudian, Roya
Abstract : A high‐performance NO2 sensor based on the 3D MoS2 aerogel is presented. Compared to single‐ or few‐layer MoS2, 3D assemblies of 2D MoS2 provide more surface area per footprint with a simple and scalable synthesis. Integration of the 3D MoS2 aerogel on a low‐power microheater platform is demonstrated, and the sensing behavior of the 3D MoS2 aerogel is investigated. A two‐step sulfurization treatment is developed to obtain a high‐quality MoS2 aerogel with strong sensing performance. The aerogel exhibits low detection limit (50 ppb) toward NO2 at room temperature, while after the two‐step sulfurization treatment, it also exhibits fast response and recovery at low heater temperature of 200 °C, with no decrease in sensitivity. The observed p‐type sensing behavior of MoS2 aerogel is investigated and identified as being controlled by the defect state (as probed by the S:Mo ratio). It is demonstrated that annealing in a hydrogen environment changes the defect state of the MoS2 aerogel by creating more sulfur vacancies; concomitantly, a transition from p‐type sensing behavior to n‐type sensing is observed. Abstract : A highly sensitive NO2 sensor based on 3D MoS2 is presented. The aerogel is integrated onto a low‐power microheater platform to investigate its sensing behavior. The sensor is ultrasensitive to NO2, with a low‐detection limit of 28 ppb. The sensing behavior is shown to be tunable by additional sulfurization treatment and hydrogen annealing.